Цивільно-правова характеристика договору зберігання на товарному складі - Демчук, А.; Demchuk, A. (Східноєвропейський національний університет ім. Лесі Українки, 2015)
У статті проведена цивільно-правова характеристика договору і його умов. Автор акцентує увагу на тому, що договір зберігання на товарному складі відноситься до групи договорів з надання послуг; обгрунтовано наступні особливості договору зберігання на товарному складі: 1) цей договір є взаємозобов'язуючим; 2) він є оплатним; 3) законодавством передбачено можливість укладення як реально, так і консенсуально договору; 4) договір має ознаки публічного договору; 5) специфіка мети договору зберігання на товарному складі проявляється в: а) забезпеченні збереження переданих на зберігання товарів; б) запобіганні шкідливого впливу об'єкта зберігання на товари інших поклажодавців; в) створенні умов, за яких під час зберігання товарів на складі їх рух у цивільному обороті міг би продовжуватися. The article considers peculiar features of contract for storage in warehouse. The author focuses on civil-legal characteristic of the contract and its terms and conditions. The author emphasizes the fact that the contract of storage in warehouses belongs to a group of contracts to provide services and describes the following features of the contract of storage in warehouses: 1) the contract of storage in warehouses has mutual binding; 2) the contract of storage in warehouses is of compensated nature; 3) taking into account the specifics of the agreement and the specific circumstances, the possibility to enter into both real and consensual agreement is provided; 4) the agreement has the characteristics of a public contract; 5) the specificity of purpose of the contract of storage in warehouses, is in the: a) securing the deposited in the warehouse goods; b) the prevention of the harmful effects of the object stored on the goods of other bailors which are stored on the same commodity stock, as well as the prevention of the harmful effects of the goods stored at the storage on the object stored and removal of the threat of appropriation of the goods by others; c) create the conditions under which during their storage in the warehouse the goods would continue their movement in public circulation. The author concludes that it is this combination of properties in the goods storage in warehouse that maximizes the efficiency of contract of such design in civil law.
Civil-legal Description of Contract for Storage in Warehouse
Keywords: цивільне право; цивільно-правовий договір; договір зберігання на товарному складі; civil law; civil contract; contract on storage in warehouses